Last twenty-five years (1980-2004) of the Residency Program in Obstetrics and Gynecology of the University of Puerto Rico: Reflexions of the Program Director and Associate Director - Adamson, Karlis; Rivera-Viñas, Juana I. (Puerto Rico Health Sciences Journal, 2010)
see manscript